Flux Control in a Defense Pathway in Arabidopsis thaliana Is Robust to Environmental Perturbations and Controls Variation in Adaptive Traits - Olson-Manning, Carrie F; Strock, Christopher F; Mitchell-Olds, Thomas (G3 : genes - genomes - genetics, 2015)
Abstract The connections leading from genotype to fitness are not well understood, yet they are crucial for a diverse set of disciplines. Uncovering the general properties of biochemical pathways that influence ecologically important traits is an effective way to understand these connections. Enzyme flux control (or, control over pathway output) is one such pathway property. The flux-controlling enzyme in the antiherbivory aliphatic glucosinolate pathway of Arabidopsis thaliana has majority flux control under benign greenhouse conditions and has evidence of nonneutral evolution. However, it is unknown how patterns of flux control may change in different environments, or if insect herbivores respond to differences in pathway flux. We test this, first through genetic manipulation of the loci that code for the aliphatic glucosinolate pathway enzymes under a variety of environments (reduced water, reduced soil nutrients, leaf wounding and methyl jasmonate treatments), and find that flux control is consistently in the first enzyme of the pathway. We also find that a generalist herbivore, Trichoplusia ni, modifies its feeding behavior depending on the flux through the glucosinolate pathway. The influence over herbivore behavior combined with the consistency of flux control suggests that genes controlling flux might be repeatedly targeted by natural selection in diverse environments and species.